Pairing Teachers for Effective Co-Teaching Teams. (2nd October 2019) - Hedin, Laura; Conderman, Greg
Abstract: Co-teaching provides the opportunity for two licensed professionals to share their expertise and differentiate instruction for a wide range of learners in a general education class. The authors describe four effective types of co-teaching partnerships and offer tips for pairing co-teachers.